Marsh Labrador Tea with spider's web on leaves- Finland - Photograph ... - Campbell, Sandy (University of Alberta Library, 2011)
Rhododendron tomentosum or Marsh Labrador Tea, is a circumpolar plant, growing across Northern North America, Nothern Europe and Asia. Traditionally, it was used as an herbal remedy. This particular plant was growing at the Santa Clause Forest, near Rovaniemi in Finland ...